2011
DOI: 10.1371/journal.ppat.1002224
|View full text |Cite
|
Sign up to set email alerts
|

Hostile Takeover by Plasmodium: Reorganization of Parasite and Host Cell Membranes during Liver Stage Egress

Abstract: The protozoan parasite Plasmodium is transmitted by female Anopheles mosquitoes and undergoes obligatory development within a parasitophorous vacuole in hepatocytes before it is released into the bloodstream. The transition to the blood stage was previously shown to involve the packaging of exoerythrocytic merozoites into membrane-surrounded vesicles, called merosomes, which are delivered directly into liver sinusoids. However, it was unclear whether the membrane of these merosomes was derived from the parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 37 publications
1
85
0
Order By: Relevance
“…PVM breakdown was previously shown to be a critical step in rodent malaria models preceding merozoite release (29)(30)(31). Furthermore, MSP1 protein expression as well as transcript abundance of the maturing merozoite markers MSP1, EBA-175, and AMA-1 at 7 days of development suggested that complete LS development had occurred.…”
Section: Frg Huhep and Frg Nod Huhep Micementioning
confidence: 88%
“…PVM breakdown was previously shown to be a critical step in rodent malaria models preceding merozoite release (29)(30)(31). Furthermore, MSP1 protein expression as well as transcript abundance of the maturing merozoite markers MSP1, EBA-175, and AMA-1 at 7 days of development suggested that complete LS development had occurred.…”
Section: Frg Huhep and Frg Nod Huhep Micementioning
confidence: 88%
“…2). The rupture of the parasitophorous vacuolar membrane (PVM) occurs first (14,66). In vitro studies indicated that PVM permeabilization is protease dependent (126,139,140).…”
Section: Budding From the Plasma Membranementioning
confidence: 99%
“…The released vesicles have been termed merosomes and are estimated to contain up to thousands of merozoites as well as host cell organelles and undefined vesicular structures (14). The merosome membrane is derived from the host cell (66). During this process, the parasite induces host cell death different from classical apoptosis or necrosis, leading to the detachment of the hepatocyte from neighboring cells (66).…”
Section: Budding From the Plasma Membranementioning
confidence: 99%
See 1 more Smart Citation
“…We generated transgenic Plasmodium berghei parasites expressing OVA either in the cytoplasm, under the control of the heat shock protein 70 (HSP70) promoter, or on the parasitophorous vacuole membrane (PVM), through fusion of OVA to the PVM protein EXP1/HEP17 (exported protein 1, hepatocyte erythrocyte protein 17 kDa) (13)(14)(15). We found that while both cytoplasmic and PVM-anchored OVA could activate OVA-specific CD8 ϩ T cells (OT-I) and CD4 ϩ T cells (OT-II), OVA fused to the PVM induced the strongest antigen-specific T-cell responses.…”
mentioning
confidence: 99%